What's in a number? The value of titers as routine proof of immunity for medical students. Issue 17 (24th April 2023) - Charlton, Carmen L.; Bailey, Ashley-Nicole M.; Thompson, L. Alexa; Kanji, Jamil N.; Marshall, Natalie C.
Highlights: Medical school admission requirements do not match national vaccination guidelines. Observed increase in requests for quantitative proof-of-immunity serology. Quantitative serology titers should not be used for asymptomatic screening. Labs are challenged to support admission requirements with inappropriate testing. Med school admission requirements should be updated to match national guidelines. Abstract: Objectives: To assess the guideline concordance of medical school requirements for students' proof-of-immunity in the United States (US) and Canada. Methods: National guidelines for healthcare worker proof-of-immunity to measles, mumps, rubella, and varicella were compared to admission requirements for 62 US and 17 Canadian medical schools. Results: All surveyed schools accepted at least one recommended form of proof-of-immunity, however, contrary to national guidelines, 16% of surveyed US schools asked for a serologic titer, and only 73–79% US schools accepted vaccination as the sole proof-of-immunity. Conclusions: The requirement of numerical, non-standardized serologic testing highlights an oversight in medical school admissions documentation. The requirement for quantitative values to demonstrate immunity is not practical from a laboratory standpoint, and is not needed to show individual immunity to these vaccine-preventable diseases. Until a more standardized process is adopted, laboratories will need to provide clear documentation and direction for quantitative titer requests.